1996
DOI: 10.1086/230995
|View full text |Cite
|
Sign up to set email alerts
|

Have American's Social Attitudes Become More Polarized?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
761
1
32

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 948 publications
(853 citation statements)
references
References 53 publications
(37 reference statements)
12
761
1
32
Order By: Relevance
“…First are actions, whether interesting in single occurrences (e.g., vote choice [Manza and Brooks 1998], first intercourse [Bearman and Bruckner 2001]) or as a recurrent pattern over time (e.g., parental investment in children [Freese and Powell 1999], political participation [Antunes and Gaitz 1975]). Second are actors' internal states, which are often regarded as interesting for what they are taken to imply for action (thinking about divorce [Huber and Spitze 1980]) or about the causality of sociocultural forces (social attitudes [DiMaggio, Evans, and Bryson 1996], perceptions of crime rates [Quillian and Pager 2001]), but sometimes are taken as an end in themselves (alienation [Kohn 1976], job satisfaction [Gruenberg 1980]). Third are aspects of actors' circumstances, which often invite interpretation as the result of iterations of individual actions and social response (educational attainment, occupational attainment, and earnings, which have been the most commonly studied individual-level outcomes over the past 30 years).…”
Section: S3mentioning
confidence: 99%
“…First are actions, whether interesting in single occurrences (e.g., vote choice [Manza and Brooks 1998], first intercourse [Bearman and Bruckner 2001]) or as a recurrent pattern over time (e.g., parental investment in children [Freese and Powell 1999], political participation [Antunes and Gaitz 1975]). Second are actors' internal states, which are often regarded as interesting for what they are taken to imply for action (thinking about divorce [Huber and Spitze 1980]) or about the causality of sociocultural forces (social attitudes [DiMaggio, Evans, and Bryson 1996], perceptions of crime rates [Quillian and Pager 2001]), but sometimes are taken as an end in themselves (alienation [Kohn 1976], job satisfaction [Gruenberg 1980]). Third are aspects of actors' circumstances, which often invite interpretation as the result of iterations of individual actions and social response (educational attainment, occupational attainment, and earnings, which have been the most commonly studied individual-level outcomes over the past 30 years).…”
Section: S3mentioning
confidence: 99%
“…Also consistent is the work of Poole and Rosenthal (2000), who documented a growing distance between the political positions of the median Democrat and the median Republican since roughly the middle 1970s. While DiMaggio et al (1996) found no evidence for a growing values divide as of the middle 1990s, analyses of more current trend data by Evans (2003) show growing evidence that "partisan" Americans (those who label themselves as liberals or conservatives) were becoming polarized around moral issues such as abortion, sexuality, school prayer (see also Mouw and Sobel, 2001;Green, 1996;Brooks, 2002;Frank, 2004;and Baldassarri and Gelman, 2008). In 1985, the mean respondent reported that he/she had discussed important matters during the past six months with 2.9 individuals out of a maximum of five.…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that citizens' policy preferences coincide with their partisanship (liberal preferences for Democrats and conservative preferences for Republicans) and the President takes position consistent with his party, then party bias would have the effect of bringing one's policy preferences into alignment with one's presidential evaluations. But, while partisanship and policy preferences have become more closely related over time, they remain far from perfectly correlated (DiMaggio et al 1996;Adams 1997;Abramowitz and Saunders 1998;Layman and Carsey 2002;Stimson 2004;Brewer 2005;Baldassarri and Gelman 2008;Bafumi and Shapiro 2009;Abramowitz 2010). Consequently, in the absence of policy updating, a commonly aspired to form of democratic accountability, whereby elected officials are evaluated on the basis of the policy positions they take rather than their partisanship, would be absent.…”
Section: Resultsmentioning
confidence: 99%
“…Factor scores based on factor analyses of the three items serve as the measure of partisanship. 17 Previous research establishes clear links between partisanship and issue preferences that have grown stronger over time, especially with regard to cultural issues (DiMaggio et al 1996;Adams 1997;Abramowitz and Saunders 1998;Layman and Carsey 2002;Stimson 2004;Brewer 2005;Baldassarri and Gelman 2008;Bafumi and Shapiro 2009;Claassen and Highton 2009;Abramowitz 2010). These patterns are evident in the data used here; the average correlation between partisanship and economic attitudes is .56; the average correlation between partisanship and cultural attitudes is .35.…”
Section: Data and Measuresmentioning
confidence: 99%